Hubungan Antara Aktifitas Fisik dan Manajemen Stres pada Mahasiswa Fisioterapi Universitas Awal Bros - Sherly Mutiara; R. Sri Ayu Indrapuri (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to explore the relationship between physical activity and stress management among physiotherapy students at Universitas Awal Bros. As students face various academic pressures and challenges, stress levels can significantly impact their overall well-being and academic performance. Physical activity has been recognized as an effective strategy for reducing stress and enhancing mental health. This research employs an analytical observational design with a cross-sectional approach, involving a sample of 20 physiotherapy students who completed questionnaires assessing their physical activity levels and stress management strategies. The International Physical Activity Questionnaire (IPAQ) was used to measure physical activity, while the Perceived Stress Scale (PSS) assessed stress levels. Preliminary results indicate that a significant portion of students engages in regular physical activity, which correlates with lower stress levels. Statistical analysis reveals a meaningful relationship between the frequency and intensity of physical activity and the effectiveness of stress management techniques among students. These findings suggest that promoting physical activity could be a valuable component in stress management programs for physiotherapy students, ultimately contributing to improved mental health and academic success